Pengaruh Pelayanan Purna Jual Terhadap Loyalitas Konsumen Pada Asus Service Center Kota Jambi - Adri Yeri Pratama Lase (Universitas Batanghari Jambi, 2019)
In the last five years the number of consumers who perform service like after-sales service, spareparts and warranty in the last five years, the service fluctuates a lot is done by consumers with different damage. The purpose o this research was to measure the after-sales service and the toyalty of consumers as ell as its influence on the Asus Service Center Kota Jambi. This research is a descriptive quantitative research and analysis tool used in this research are simple linear regression is useful to see the direction of the relationship between the variable bound against free. For the purpose of answering the purpose number 2 used statistical test t. The correlation coefficient to know how the relationship between variables and coefficients of determination of useful to see the magnitude of the influence of the variable bound against free.Asus manuactures a wide array of IT product, putting yourself as a company producing product with after-sales service. This is evidenced by the numerous awards he has held both in the aspect o desain, type, and quality of product. The calculation SPSS Y = 8,983 + 0,208 X + e of the equations looks positive influence between after-sales service (X) on loyalty consumers (Y) at the Asus Service Center Kota Jambi. From the result of the obtained values SPSS (coefficient) r2 this figure amounted 78,5% states that the variable after-sales service (X) is able to explain the variabel loyalti consumers (Y) is 78,5% and the remaining 21,5% is explained by other factors which is not included in the research model. After-sales service partially influence on consumers loyalty this is demonstrated from the significant value that is smaller than the value of alpha. This means that the hyotesis in this research was received.